2023
DOI: 10.21203/rs.3.rs-2472194/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Heuristics and Biases in Complex Choices

Abstract: Many choices are complex. These choices entail consideration of multiple variables characterized by non-linear interactions. Prior research into the complex choice process of people neglects two categories of major choice determinants: heuristics and biases. This research takes on the challenge of integrating such behavior determinants into the study of complex choices. We do so using a new experimental paradigm in which participants tune on-screen dials that represent choice variables. Through their tuning ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Since this behavior would likely have an outsized impact on any analysis, we decided to remove this participant from the data set, leaving 397 observations. We report participants' solo efforts in a companion paper (Gurney, Miller, and Pynadath 2023). We found that when working alone, the four-peak landscapes were more challenging than the one-peak, that both anchoring and framing yielded significant main effects on participants' choice quality, and that doing the one-peak task first was correlated with better outcomes on the four-peak task.…”
Section: Data and Analysesmentioning
confidence: 92%
See 1 more Smart Citation
“…Since this behavior would likely have an outsized impact on any analysis, we decided to remove this participant from the data set, leaving 397 observations. We report participants' solo efforts in a companion paper (Gurney, Miller, and Pynadath 2023). We found that when working alone, the four-peak landscapes were more challenging than the one-peak, that both anchoring and framing yielded significant main effects on participants' choice quality, and that doing the one-peak task first was correlated with better outcomes on the four-peak task.…”
Section: Data and Analysesmentioning
confidence: 92%
“…A blossoming corner of behavioral science is working to understand the nuance of human judgment and decision making during complex choice. A complex choice is one in which the relationships between the variables under consideration are nonlinear, which means that even when a choice is characterized by a small number of variables, their interactions can render optimization intractable (Gurney, Miller, and Pynadath 2023). Obvious examples of complex choices are home buying, career moves, and mate selection.…”
Section: Related Work Complex Choicesmentioning
confidence: 99%
“…Since this behavior would likely have an outsized impact on any analysis, we removed this participant from the data set, leaving 397 observations. We report participants' solo efforts in a companion paper (Gurney, Miller, and Pynadath 2023). We found that when working alone, the four-peak landscapes were more challenging than the one-peak, that both anchoring and framing yielded significant main effects on participants' choice quality, and that doing the one-peak task first was correlated with better outcomes on the four-peak task.…”
Section: Data and Analysesmentioning
confidence: 92%
“…A complex choice is one in which the relationships between the variables under consideration are nonlinear. Such a relationship means that even when only a few variables characterize a choice, their interactions can render optimization intractable (Gurney, Miller, and Pynadath 2023). Obvious examples of complex choices are home buying, career moves, and mate selection.…”
Section: Related Work Complex Choicesmentioning
confidence: 99%